GERAKAN DAKWAH DALAM UPAYA PENCEGAHAN DINI TERHADAP PENYEBARAN DAN PENERIMAAN ISLAMISME KELOMPOK RADIKAL- TERORISME DI LAMPUNG - Syukur, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2015)
DA’WAH AS THE EARLY PREVENTION EFFORTS AGAINST THE SPREAD AND ACCEPTANCE OF ISLAMISM IN RADICAL TERRORISM IN LAMPUNG: This paper is set out from the anxiety if the anarchism in term of acceptance and the spread of Moslem which is done by certain group of salafi in Lampung as the response of the democracy process after reformation era in order to face the political ideology that is pro- democracy and contra with democracy. With a practical analysis, the authors found that the construction of narrative Islamism developed by radical groups in society Lampung only radical Moslem didn’t lead to radicalism and terrorism. The number of the radical group is small. The narratives Islamism spread by radical groups with different patterns of deployment and distribution factors by which identifying and facilitating the transmission of Islamism is generally not accepted by the majority of the Islamic community in Lampung. Most of Lampung people lead the moderate Islamic and cultural Lampung Piil Pesanggiri and Adat Muakhi which are rejected the terrorism.